Exploring host resistance against chilli leaf curl disease in a tolerant chilli genotype - Mangal, Manisha; Srivastava, Arpita; Mandal, Bikash; Solanki, Vikas; Mirajkar, Shriram J.; Shashank, Pathour R.; Kalia, Pritam; Rana, Jai Chand; Sharma, Vinod Kumar (MDPI, 2024)
In tropical countries, combating leaf curl disease in hot peppers has become important in improvement programs. Leaf curl disease is caused by whitefly (Bemisia tabaci) transmitted begomoviruses, which mainly include chilli leaf curl virus (ChiLCV). However, multiple begomoviruses have also been found to be associated with this disease. The Capsicum annuum line, DLS-Sel-10, was found to be a tolerant source against this disease during field screening. In this study, we characterized the resistance of DLS-sel-10 against chilli leaf curl virus (ChiLCV) in comparison to the susceptible cultivar Phule Mukta (PM), focusing on the level, stage, and nature of resistance. Comprehensive investigations involved screening of DLS-Sel-10 against the whitefly vector ChiLCV. The putative tolerant line displayed reduced virus infection at the seedling stage, with increasing resistance during vegetative, flowering, and fruiting stages. Both DLS-Sel-10 and PM could be infected with ChiLCV, although DLS-Sel-10 remained symptomless. Insect feeding assays revealed DLS-Sel-10 as a less preferred host for whiteflies compared to PM. In conclusion, DLS-Sel-10 demonstrated tolerance not only to ChiLCV but also served as an unfavorable host for the whitefly vector. The study highlighted an age-dependent increase in tolerance within DLS-Sel-10, showcasing its potential for effective leaf curl disease management in chilli.